The Sundanese Comic Ririwa Nu Mawa Pati - An Intertext of Sundanese - Islam Cosmology - Kasmana, Kankan; Sabana, Setiawan; Gunawan, Iwan; Ahmad, Hafiz Aziz (Mudra Jurnal Seni Budaya, 2018)
Ririwa nu Mawa Pati, the Sundanese strip comic with horror genre, published by â€œMangleâ€, a Sundanese cultural magazine in West Java, 1922. The comic consist of material about belief in the supernatural being in the Sundanese society at that time. This research attempts to find expressions of Sundanese human death journey conception derived from oral literature of selected informants in the comics as an intertext in an effort to understand and interpret the comics in depth. This is a qualitative research, intertextual analysis is used to find representations of cultural texts embodied in selected comic elements. The results of the analysis reveal the existence of oral literature absorption (hypogram) in the form of core and development in the comic as transition work, present explicitly through storyline, comic element in the form of dialogue in word balloons, description panel, and visual scene of the characters. Comics become a representation of the view of the comic artist about the world around the visible (or tangible) and invisible (or intangible). Ririwa nu Mawa Pati, komik strip Sunda bergenre horor diterbitkan oleh majalah sastra dan budaya Sunda Mangle di Jawa Barat tahun 1992. Komik ini sarat materi mengenai kepercayaan akan mahluk halus di masyarakat Sunda saat itu. Penelitian berupaya menemukan ungkapan konsep fase perjalanan kematian manusia Sunda yang berasal dari sastra lisan informan terpilih yang ada dalam komik sebagai sebuah interteks sebagai upaya agar dapat memahami dan memaknai komik secara mendalam. Penelitian bersifat kualitatif, analisis intertekstual digunakan untuk menemukan representasi teks budaya yang mewujud dalam unsur komik terpilih. Hasil analisis mengungkapkan adanya serapan satra lisan (hypogram) baik berupa inti maupun pengembangan dalam komik ini sebagai karya transisi, hadir secara tersurat melalui alur cerita, unsur teraga komik berupa dialog balon kata, panel keterangan, serta visual adegan para tokohnya. Komik menjadi representasi kosmologi Sunda dan pandangan komikus mengenai dunia sekitarnya baik yang kasat mata maupun yang tak terlihat. Kosmologi Sunda tidak hanya dipandang sebagai pemisahan dunia, namun difahami pula sebagai fase perjalanan kehidupan dan kematian manusia Sunda.Â 